2020
DOI: 10.1038/s41563-020-0620-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic proximity and nonreciprocal current switching in a monolayer WTe2 helical edge

Abstract: The integration of diverse electronic phenomena, such as magnetism and nontrivial topology, into a single system is normally studied either by seeking materials that contain both ingredients, or by layered growth of contrasting materials 1-9 . The ability to simply stack very different twodimensional (2D) van der Waals materials in intimate contact permits a different approach 10,11 . Here we use this approach to couple the helical edges states in a 2D topological insulator, monolayer WTe2 12-16 , to a 2D laye… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Note that the method by increasing the layer thickness for better effect does not apply to all 2D HS system. For example, in the WTe 2 /CrI 3 HS, the conductance of WTe 2 depends on the nearest CrI 3 layer and is not affected by the CrI 3 thickness 62 . The impact of the polarization intensity in In 2 Se 3 on the magnetism in LaCl is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the method by increasing the layer thickness for better effect does not apply to all 2D HS system. For example, in the WTe 2 /CrI 3 HS, the conductance of WTe 2 depends on the nearest CrI 3 layer and is not affected by the CrI 3 thickness 62 . The impact of the polarization intensity in In 2 Se 3 on the magnetism in LaCl is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study using immense pressures revealed that the antiferromagnet-ferromagnet switching is not a result of the interlayer coupling, but due to stacking order differences in CrBr 3 41 . Looking forward, a recent publication shows the coupling of ferromagnetism and topological states introduces controllable currents in helical edge states in CrI 3 and WTe 2 heterostructures 42 , suggesting an interesting future in the heterostucture design of 2D magnetic materials.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with topological superconductivity, such a 1D system may carry Majorana bound states at the topological phase-boundary between trivial and helical parts of the edge, [219,220] as discussed in the following section. With relevance to atomically thin QSH insulators in particular, magnetic fields may be locally imposed by ferromagnetic materials [59,221] proximal to the QSH edge, such as ferromagnetic clusters [59] or even layered ferromagnets and ferromagnetic insulators, [221][222][223][224][225][226][227][228] the latter of which are fields that have burgeoned over the last three years. Layered ferromagnets exhibit intrinsic ferromagnetism in which each layer has a uniform magnetic polarization, even down to the monolayer limit, some of which are stable up to room temperature [223] and can be switched [223] between ferromagnetic and paramagnetic states with an applied gate voltage.…”
Section: Tunability By Magnetic Fieldsmentioning
confidence: 99%
“…Layered ferromagnets exhibit intrinsic ferromagnetism in which each layer has a uniform magnetic polarization, even down to the monolayer limit, some of which are stable up to room temperature [ 223 ] and can be switched [ 223 ] between ferromagnetic and paramagnetic states with an applied gate voltage. A layered ferromagnet recently demonstrated [ 221 ] strong, polarization‐dependent modulation of the edge conductance in the QSH material WTe 2 , holding great promise as a “topological switch.”…”
Section: Potential Applications Of Atomically Thin Qsh Materialsmentioning
confidence: 99%